Analisis Implementasi Pengelolaan Keselamatan Kerja Perawat Era Pandemi Covid-19 pada Rumah Sakit Sabah Kuwait - Noerlaeli Ono Sutisna; Edison C Sembiring; Soehatman Ramli (Journal of Applied Management Research, 2022)
ABSTRAKThis study aims to measure the implementation of safety management for nurses' work safety culture with a cross-sectional design that analyzes the implementation of nurses' safety management for nurses' safety culture in the Covid-19 pandemic era at Kuwait's Sabah Hospital. The research sample was 110 nurses who worked in 2 Covid-19 female inpatient rooms and 2 Covid-19 male inpatient rooms using the total sampling method. Collecting information by using a Likert scale questionnaire. The results of the study on the perception of OSH management in the nurse's work safety culture personal dimensions of 42.79 (68%) with good category, behavioral dimensions of 44.51 (69%) in good category, and organizational dimensions of 36.57 (56%) with poor category. The results of OSH aspects that affect the implementation of OHS management in work safety culture personal dimensions on teamwork (1459) in the very good category, training (488) in the very good category, reporting (1416) in the good category, work environment (1344) with good category. Dimensions of behavior on the aspect of compliance (2456) with a very good category, the use of PPE (1464) with a very good category, communication (976) with a very good category. Organizational dimensions in the regulatory aspect (2119) in good category, leadership (1494) in good category, risk (410) in good category. It was concluded that the implementation of nurse safety management for work safety culture in the era of the covid-19 pandemic at the level of work safety culture was displayed from 3 dimensions with a total score of 1.78 for nurses' safety culture maturity level located at level 2 (managing). The results of this study are expected to be data for hospitals in order to further improve the management of work safety in the work safety culture of nurses so that they can improve the quality of health services in hospitals.Keywords: Occupational Safety Management, Work Safety Culture, Nurses.ABSTRAKPenelitian ini bertujuan untuk mengukur implementasi pengelolaan keselamatan kerja untuk budaya keselamatan kerja perawat dengan desain cross- sectional yang menganalisis implementasi pengelolaan keselamatan kerja perawat untuk budaya keselamatan kerja perawat di era pandemic Covid- 19 di rumah sakit Sabah Kuwait. Sampel penelitiannya adalah perawat berjumlah 110 orang yang bekerja di 2 ruang rawat inap wanita Covid- 19 dan 2 ruang rawat inap pria Covid- 19 dengan memakai metode pengambilan sampel total sampling. Pengumpulan informasi dengan memakai kuesioner skala likert. Hasil penelitian pada persepsi pengelolaan K3 di budaya keselamatan kerja perawat dimensi personal sebesar 42.79 (68%) dengan kategori baik, dimensi prilaku sebesar 44.51 (69%) dengan kategori baik, dan dimensi organisasi sebesar 36.57 (56%) dengan kategori kurang baik. Hasil dari aspek- aspek K3 yang mempengaruhi implementasi pengelolaan K3 di budaya keselamatan kerja dimensi personal pada kerja sama tim (1459) dengan kategori sangat baik, pelatihan (488) dengan kategori sangat baik, pelaporan (1416) dengan kategori baik, lingkungan kerja (1344) dengan kategori baik. Dimensi prilaku pada aspek kepatuhan (2456) dengan kategori sangat baik, pemakaian APD (1464) dengan kategori sangat baik, komunikasi (976) dengan kategori sangat baik. Dimensi organisasi pada aspek regulasi (2119) dengan kategori baik, kepemimpinan (1494) dengan kategori baik, resiko (410) dengan kategori baik. Disimpulkan implementasi pengelolaan keselamatan kerja perawat untuk budaya keselamatan kerja di era pandemic covid- 19 pada tingkatan level budaya keselamatan kerja ditampilkan dari 3 dimensi dengan total skor maturity level budaya keselamatan kerja perawat sebesar 1. 78 terletak di level 2 (managing). Hasil penelitian ini diharapkan bisa jadi data untuk rumah sakit agar lebih meningkatkan pengelolaan keselamatan kerja di budaya keselamatan kerja perawat sehingga bisa meningkatkan mutu pelayanan kesehatan di rumah sakit.Kata Kunci: Pengelolaan Keselamatan Kerja, Budaya Keselamatan Kerja, Perawat.